2021
DOI: 10.21076/vizyoner.873996
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of the Effect of Tourist Guides’ Work Values on Their Work Engagement

Abstract: Araştırmanın temel amacı, turist rehberlerinin sahip oldukları iş değerlerinin işe adanmışlıkları üzerindeki etkisinin belirlenmesidir. Bu doğrultuda turist rehberlerinin iş değerleri ve işe adanmışlık düzeylerinin tespit edilmesi ve ilişkilerinin incelenmesi, mesleki açıdan birtakım beklentileri karşılamaya yönelik adımlar atılması için önem taşımaktadır. Araştırma kapsamında anket tekniği kullanılmış, veriler 311 turist rehberinden elde edilmiştir. Turist rehberlerinin iş değerlerini tespit etmek amacıyla El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is thought that the increase in professional experience is effective in forming this significant differentiation. On the other hand, there are studies in the literature that found that work engagement does not differ according to age variable (Asmadili, 2020;Atalık, 2021;Bostancı & Ekiyor, 2015;Güneş, 2022;Turgut, 2011). In the study, the work engagement levels of teachers with postgraduate education were found to be higher than those of teachers with undergraduate degrees.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the increase in professional experience is effective in forming this significant differentiation. On the other hand, there are studies in the literature that found that work engagement does not differ according to age variable (Asmadili, 2020;Atalık, 2021;Bostancı & Ekiyor, 2015;Güneş, 2022;Turgut, 2011). In the study, the work engagement levels of teachers with postgraduate education were found to be higher than those of teachers with undergraduate degrees.…”
Section: Discussionmentioning
confidence: 99%